2021
DOI: 10.3390/cancers13061311
|View full text |Cite
|
Sign up to set email alerts
|

Targeting Chronic Myeloid Leukemia Stem/Progenitor Cells Using Venetoclax-Loaded Immunoliposome

Abstract: CML is a hematopoietic stem-cell disorder emanating from breakpoint cluster region/Abelson murine leukemia 1 (BCR/ABL) translocation. Introduction of different TKIs revolutionized treatment outcome in CML patients, but CML LSCs seem insensitive to TKIs and are detectable in newly diagnosed and resistant CML patients and in patients who discontinued therapy. It has been reported that CML LSCs aberrantly express some CD markers such as CD26 that can be used for the diagnosis and for targeting. In this study, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 51 publications
(42 reference statements)
1
17
0
Order By: Relevance
“…CD26 (DPPV) has also proved to be a novel, specific biomarker for CML LSCs, which is promising for the diagnosis and targeted treatment of CML (161)(162)(163). In a recent study, a venetoclax-loaded immunoliposome remarkably induced apoptosis in CD26+ cells in both stem cells and progenitor cells population (164). However, DPPIV blocker vildagliptin in combination with nilotinib did not exert a synergy effect, indicating insignificant effects of co-administration (165).…”
Section: Targeting Lscs Via Surface Markersmentioning
confidence: 99%
“…CD26 (DPPV) has also proved to be a novel, specific biomarker for CML LSCs, which is promising for the diagnosis and targeted treatment of CML (161)(162)(163). In a recent study, a venetoclax-loaded immunoliposome remarkably induced apoptosis in CD26+ cells in both stem cells and progenitor cells population (164). However, DPPIV blocker vildagliptin in combination with nilotinib did not exert a synergy effect, indicating insignificant effects of co-administration (165).…”
Section: Targeting Lscs Via Surface Markersmentioning
confidence: 99%
“…BCL2 is overexpressed and hyperactivated in CML LSCs [48] and BCL2 targeting was indeed found to reduce LSC engraftment in mice [49]. Houshmand et al [47] found that their immunoliposome could indeed reduce cell growth and induce apoptosis in CD26+ cell lines, and co-administration with TKIs (imatinib, nilotinib) demonstrated synergistic effects. Moreover, they observed that their immunoliposome could dramatically reduce the percentage of CD26+ cells in primary patient samples.…”
Section: Aberrant Surface Markers In CML Lscs and Their Diagnostic Predictive And Therapeutic Rolementioning
confidence: 99%
“…However, a preclinical study evaluating the combination of TKIs (imatinib or nilotinib) with vildagliptin failed to evidence major cooperative effects on engraftment in mice models [46]. More recently, Houshmand et al [47] developed an innovative strategy based on a liposome loaded with the BCL2 inhibitor venetoclax exploiting begelomab (an anti-CD26 antibody) to selectively target CD26+ CML LSCs. BCL2 is overexpressed and hyperactivated in CML LSCs [48] and BCL2 targeting was indeed found to reduce LSC engraftment in mice [49].…”
Section: Aberrant Surface Markers In CML Lscs and Their Diagnostic Predictive And Therapeutic Rolementioning
confidence: 99%
“…Furthermore, BCL-2 inhibitors (subutoclax and venetoclax) can increase the eradication of CML LSCs by disrupting energy metabolic pathways [ 208 , 209 ]. Recently, an innovative strategy based on a liposome loaded with the BCL2 inhibitor (venetoclax) using an anti-CD26 antibody (begelomab) to selectively target CML LSCs showed that the immunoliposome could reduce cell growth and also induce apoptosis in CD26 + LSCs, along with synergistic effects by coadministration with imatinib or nilotinib [ 210 ]. Interestingly, inhibition of ALOX15 pathway involved in fatty acid metabolism with the BLT2-specific inhibitor triggered apoptosis and inhibited self-renewal in TKI-resistant CML cells in blast crisis phase [ 211 ].…”
Section: Therapeutic Implications Of CML Lscsmentioning
confidence: 99%